Upaya Penguatan Kualitas Pendidikan Melalui Sharing Session-Motivasi Studi Lanjut - Arditya Prayogi; Rhischa Assabet Shilla; Imam Prayogo Pujiono; Riki Nasrullah (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Education is the main pillar of national development that contributes to improving the quality of human resources. However, the high cost of education, especially at the tertiary level, is a significant challenge. To overcome this obstacle, scholarship programs such as LPDP, Fulbright, and DAAD are present as a solution, opening access for the younger generation to continue their studies at the international level. This article discusses the implementation of a sharing session activity that aims to motivate undergraduate and master's graduates to continue their studies through scholarships. This activity is designed interactively with materials including strategies for obtaining scholarships, document preparation, and the development of soft skills and language skills. Based on the implementation, this activity succeeded in increasing the motivation and understanding of the participants, which was reflected in the enthusiasm in the discussion and activeness during the session. Positive impacts were seen in the cognitive, affective, and psychomotor abilities of the participants. It is hoped that this activity will not only encourage individuals to achieve higher education but also produce a globally competitive generation that is able to contribute to national development. Thus, this kind of program is a strategic step in advancing education and creating a more empowered and prosperous society.